GC-MS-FID characterization and antibacterial activity of the Mikania cordifolia essential oil and limonene against MDR strains. (February 2020) - Justino de Araújo, Ana Carolina; Freitas, Priscilla Ramos; Rodrigues dos Santos Barbosa, Cristina; Muniz, Débora Feitosa; Rocha, Janaína Esmeraldo; Albuquerque da Silva, Ana Cristina; Datiane de Morais Oliveira-Tintino, Cícera; Ribeiro-Filho, Jaime; Everson da Silva, Luiz; Confortin, Camila; Amaral, Wanderlei do; Deschamps, Cícero; et al.
Abstract: The present study evaluated the effect of the essential oil of Mikania cordifolia (EOMc) and its major constituent limonene alone or associated with antibacterial drugs against Multidrug Resistant Bacteria (MDR). To evaluate the antibacterial activity, the minimum inhibitory concentrations (MIC) of the oil and limonene against Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus were determined. The antibiotic-modulating activity was assessed using subinhibitory concentrations (MIC/8) of these substances in combination with conventional antibacterial drugs. Although no relevant antibacterial activity of the natural products was detected, both substances modulated the action of antibiotics against resistant bacteria. The EOMc demonstrated the best modulating effect against P. aeruginosa, presenting synergistic effects when associated with gentamicin and norfloxacin. In addition, the oil reduced the MIC of norfloxacin against E. coli as well as reduced the MIC of gentamicin against S. aureus . On the other hand, the best effect of limonene was obtained against S. aureus . Thus, it is concluded that the essential oil Mikania cordifolia and the isolated compound limonene do not have clinically significant antibacterial effect, but modulate the action of antibiotics against MDR bacteria.